Grain-Boundary Resistance and Nonlinear Coefficient Correlation for SnO2-Based Varistors - Masteghin, Mateus Gallucci [UNESP]; Orlandi, Marcelo Ornaghi [UNESP] (Univ Fed Sao Carlos, Dept Engenharia Materials, 2016)
This work has focused on the electrical and microstructural properties of Nb2O5-doped SnO2-MnO2 ceramics. The pellets were prepared by solid-state reaction method according to the system (99.5-x) SnO2 - 0.5 MnO2 - (x) Nb2O5, on the following molar ratio x = 0.05; 0.10; 0.15; 0.20 and 0.25. Scanning electron microscopy and electrical measurements (ac and dc) were used to study the materials properties. The results showed that the increase of Nb2O5 content in the SnO2-MnO2 matrix has led to an increase in the varistor properties. A detailed study of the electrical properties of materials was conducted using impedance spectroscopy and the results indicated that Nb2O5 has a tendency to form an electron trapping level near the conduction band. In order to explain these findings, a parallel equivalent circuit model was used to simulate the values of the grain boundary resistance. A close relationship was found between the value of the nonlinear coefficient and the grain boundary resistance for the studied varistors, where both values increased with increasing the amount of Nb2O5, which is important for practical applications.
Keywords: Varistor; Tin oxide; Electrical properties; Impedance spectroscopy